Anxiety Symptoms After Orthopedic Injury: A Systematic Review. Issue 1 (January 2021) - Breazeale, Stephen; Conley, Samantha; Gaiser, Edward; Redeker, Nancy S.
Abstract : Background: Millions of Americans are injured each year, with 75% suffering orthopedic injuries. Those with orthopedic injury often experience postinjury symptoms, such as anxiety, that negatively influence long-term outcomes. The purpose of this systematic review was to evaluate (1) the prevalence of anxiety symptoms chronologically in relation to time of orthopedic injury, (2) the associations of anxiety symptoms with other symptoms in individuals with orthopedic injury, and (3) the associations between anxiety symptoms and functional performance and mental health outcomes in individuals with orthopedic injury. Methods: The databases CINAHL, Ovid MEDLINE, Ovid PsycInfo, Ovid Embase, ProQuest, and ClinicalTrials.gov were searched on June 25, 2020. Studies were selected for review if (1) participants were 16 years or older, (2) the prevalence of anxiety symptoms was listed, (3) anxiety symptoms were assessed using a validated instrument, (4) the study was published in English, and (5) more than 50% of the participants suffered orthopedic injury to the appendicular skeleton or pelvic ring. Results: Anxiety symptoms were present in 11.5%–55.9% of individuals up to 10 years after orthopedic injury and often co-occurred with those of depression, pain, and posttraumatic stress disorder to negatively influence functional performance and mental health outcomes. Conclusions: Anxiety symptoms post-orthopedic injury are highly prevalent and persistent. Anxiety symptoms are associated with other distressing symptoms and influence long-term outcomes. These findings highlight the need to screen for and treat anxiety symptoms following orthopedic injury and may help in designing future self-management interventions. Abstract : Supplemental Digital Content is Available in the Text.